Self-dispersible nanocrystals of albendazole produced by high pressure homogenization and spray-drying. (2nd October 2016) - Paredes, Alejandro Javier; Llabot, Juan Manuel; Sánchez Bruni, Sergio; Allemandi, Daniel; Palma, Santiago Daniel
Abstract: Albendazole (ABZ) is a broad-spectrum antiparasitic drug used in the treatment of human or animal infections. Although ABZ has shown a high efficacy for repeated doses in monogastric mammals, its low aqueous solubility leads to erratic bioavailability. The aim of this work was to optimize a procedure in order to obtain ABZ self-dispersible nanocrystals (SDNC) by combining high pressure homogenization (HPH) and spray-drying (SD). The material thus obtained was characterized and the variables affecting both the HPH and SD processes were studied. As expected, the homogenizing pressure and number of cycles influenced the final particle size, while the stabilizer concentration had a strong impact on SD output and redispersion of powders upon contact with water. ABZ SDNC were successfully obtained with high process yield and redispersibility. The characteristic peaks of ABZ were clearly identified in the X-ray patterns of the processed samples. A noticeable increase in the dissolution rate was observed in the aqueous environment.